ANALISIS PENGENDALIAN PENYAKIT DBD SESUAI PERATURAN DAERAH KOTA SEMARANG NOMOR 5 TAHUN 2010 TENTANG PENGENDALIAN PENYAKIT DEMAM BERDARAH DENGUE DI KECAMATAN TEMBALANG - Rahmawati, Feby; Sriatmi, Ayun; Jati, Sutopo Patria (Jurnal Kesehatan Masyarakat (Undip), 2016)
Dengue Hemorrhagic Fever (DHF) is still one of the major public health problem in Indonesia. The development of this disease from tends to increase every year, both from the number of cases or the distribution area. Outbreaks of dengue fever also occurs in the city of Semarang, extraordinary events (KLB) DBD The Semarang occurred in the year 2010 reached 5,556 cases. This makes the government of Semarang issued a local regulation No. 5 of 2010 on Control of Dengue Fever in the context of prevention of Extraordinary Events (KLB) DBD City Semarang.Tujuan of this study was to conduct analysis of dengue control implementation according Semarang City Regulation No. 5 year 2010 on the control of dengue hemorrhagic fever in the district Tembalang. This type of research is research exploratory research with qualitative approach. The data collection is done by in-depth interviews using interview guide. Informants research that includes Chief Kedungmundu PHC, PHC Chief Rowosari, business Dengue Control Program Kedungmundu Health Center and Health Center Program Management Control DBD Rowosari. Head of P2P Sector Semarang City Health Office, District Tembalang Head, Head Village Tembalang, Bulusan village headman, village headman Sendangmulyo and Village headman Sendangguwo. The results showed that the implementation Control of Dengue fever in accordance Regional Regulation of Semarang Semarang No. 5 of 2010 on Control of Dengue are still not running well because in terms of communication still lack the socialization of the regulation to the executive officer and the community and in the disposition is still a lack of willingness officer implementers to learn about these regulations. As for the terms of the resources and SOP also not completely worked well because of the lack of understanding regarding the executive officer of the regulation. City Health Office to intensify again over the socialization of the study showed that of Regional Regulation of Semarang Semarang No. 5 of 2010 on Control of dengue.